Effect of bolster suspension parameters of three-piece freight bogie on the lateral frame force. Issue 1 (2nd January 2020) - Pandey, M.; Bhattacharya, B.
ABSTRACT: Monitoring of lateral frame forces caused by the Rail vehicles is becoming increasingly important as both speeds and loads are increasing along with putting in more continuous welded rail in use. In this study on a freight wagon fitted with three-piece bogies, the effect of bogie lateral stiffness, snubbing force and wedge coefficient of friction on the lateral frame force is presented. A multibody model in NUCARS consisting of 11 rigid bodies and 49 dof's has been made for performing simulation analysis on 30 different bolster suspension combinations. The simulation results suggest that increasing the snubbing force and/or the wedge coefficient of friction increase the lateral frame forces in general. Increasing the lateral stiffness of the bogie along with the snubbing force cause increase in the lateral frame force. The lateral frame force depends upon the relative interplay of the lateral bogie stiffness and the snubbing force for the subject suspension designs.